2011
DOI: 10.1093/humrep/der255
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs are associated with human embryo implantation defects

Abstract: To our knowledge, this is the first study to evaluate the differential expression of miRNAs in the secretory endometrium of RIF-IVF patients. We suggest that the RIF-associated miRNAs could be exploited as new candidates for diagnosis and treatment of embryo implantation failures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
152
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(154 citation statements)
references
References 44 publications
1
152
0
1
Order By: Relevance
“…A number of miRNAs have been detected in the endometrium at the time of implantation in mice or at mid-secretory phase, the receptive window, in humans (Chakrabarty et al 2007, Hu et al 2008, Revel et al 2011. Among these miRNAs, some are predicted or proved to target genes that are critical for embryo implantation, including COX2 (Chakrabarty et al 2007), HOXA10 (Estella et al 2012), LIF (Altmae et al 2013), as well as WNT signaling (Revel et al 2011, Altmae et al 2013, p53 signaling components (Revel et al 2011, Altmae et al 2013. However, despite their recognized roles in embryo implantation, how the dynamic expression of miRNAs is controlled during implantation remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of miRNAs have been detected in the endometrium at the time of implantation in mice or at mid-secretory phase, the receptive window, in humans (Chakrabarty et al 2007, Hu et al 2008, Revel et al 2011. Among these miRNAs, some are predicted or proved to target genes that are critical for embryo implantation, including COX2 (Chakrabarty et al 2007), HOXA10 (Estella et al 2012), LIF (Altmae et al 2013), as well as WNT signaling (Revel et al 2011, Altmae et al 2013, p53 signaling components (Revel et al 2011, Altmae et al 2013. However, despite their recognized roles in embryo implantation, how the dynamic expression of miRNAs is controlled during implantation remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…In general, miRNAs are spatiotemporally expressed and, by binding to 3 0 UTRs of their targeting mRNAs to induce mRNA degradation or translation repression, they are able to fine tune the expression of a series of their target genes and influence multiple physiological and pathological processes (He & Hannon 2004, Du & Zamore 2005, Ouellet et al 2006, Nilsen 2007. In fact, miRNAs are emerging as a group of gene-expression modulators critically involved in embryo implantation (Chakrabarty et al 2007, Hu et al 2008, Nagaraja et al 2008, Revel et al 2011. They have been shown to exhibit dynamic temporal and spatial expression in both the uterus and the blastocyst during implantation (Hossain et al 2012, Su et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…LRP-6 and FZD6 expressions are also present in human endometrium and determined to be equally expressed in proliferative and secretory phase endometrium [28]. Wnt receptor related proteins were also found to be associated with endometrial functions, since mRNA levels of sFRP4 were found to be lower during the secretory phase of the menstrual cycle in repeated implantation failure (RIF) endometrium [36].…”
Section: Wnt Signaling In Uterine Receptivitymentioning
confidence: 99%
“…To date, 19 secreted cysteinerich Wnt ligands, ten transmembrane, G-protein coupled frizzled receptors (FZD), two low-density lipoprotein receptor-related protein co-receptors (LRP5/6), two receptor tyrosine kinase-like orphan receptors (ROR1/2) and receptor-like tyrosine kinase (RYK) have been identified in the mammalian Wnt family [14,15]. Based on the involvement of certain intracellular players, the Wnt signaling system can be divided into either b-catenin-dependent or b-catenin-independent pathways [16,17]. It is also important to bear in mind that the two aforementioned signaling pathways are highly interconnected and they cross-regulate each other [18].…”
Section: General Introduction Of Wnt Signalingmentioning
confidence: 99%
“…1b). In detail, Wnt stimulation induces phosphorylation of LRP and Dsh and disruption of Axin/APC/GSK3b/CK1a destruction complex, and finally leads to impaired degradation and accumulation of b-catenin in the cytosol [16,25]. Thus, accumulated b-catenin translocates to the nucleus and serves as a transcriptional co-regulator of Wnt target genes.…”
Section: General Introduction Of Wnt Signalingmentioning
confidence: 99%